Shallow water habitats provide high-quality foraging environments for the Spoon-billed Sandpiper at a critical staging site - Lili Sun; Hongyan Yang; Xiuyuan Lu; Ting Fu; Jia Guo; Sicheng Ren; Waner Liang; Qing Chen; Dongming Li; Theunis Piersma; Nicola Crockford; Yifei Jia; et al. (Avian Research, 2025)
Abundant food supply is crucial for the survival of long-distance migratory birds. The continued population decline of the Spoon-billed Sandpiper (Calidris pygmeae), a critically endangered shorebird, is primarily attributed to habitat loss and degradation. However, significant gaps remain in research on their diet and foraging habitat selection, limiting effective conservation and restoration efforts. In this study, we investigated the composition of macrobenthic communities, analyzing habitat and prey selection at the main foraging area of SBS in Tiaozini, Jiangsu Province of eastern China—their most critical staging site during southward migration. Our findings revealed 25 species of macrobenthos in foraging areas, with mobile epibenthos comprising the largest group by biomass, accounting for 73%, and having higher density and biomass nearshore. Observations of foraging Spoon-billed Sandpiper individuals indicated that shallow water habitats were their preferred foraging environments, where mobile epibenthos, which thrive in these habitats after the tide recedes, made up 81% of their biomass intake. We propose that shallow water habitats in intertidal mudflats serve as essential refuges for mobile epibenthos after tidal retreat, thereby providing Spoon-billed Sandpipers with access to high-quality food resources. Habitat protection efforts should prioritize habitats harboring extensive microhabitats with shallow water, especially the nearshore area, and further research is needed to explore the mechanisms underlying the formation of these microhabitats, with the ultimate goal of restoring more high-quality habitats for the Spoon-billed Sandpiper.